Effect of motor imagery training on hand function and upper limb coordination in children with hemiplegic cerebral palsy - Mennatallah Hesham Ahmed Fawzy; Zeinab Ahmed Hussein; Abdelrahman Abdelrazek; Walaa A. Abd El-Nabie (2024)
Background: Both impairment of hand function and upper limb coordination are the main problems facing children with hemiplegic cerebral palsy. Purpose: The present study aims to evaluate the effect of motor imagery on hand function and upper limb coordination in children with hemiplegic cerebral palsy. Methods: Thirty-six children with hemiplegic cerebral palsy ranging in age from seven to twelve years participated in this study and were recruited from Outpatient Clinics of Physical Therapy Faculty of Cairo University. They were randomly allocated to one of two groups(3, (Bcontrol, and study. Children in both groups received a designed physical therapy program in addition, children in control group received tailored occupational therapy program to improve hand function and upper limb coordination, while children in study group received motor imagery training. Treatment program was conducted for both groups for one hour, three sessions per week for twelve consecutive weeks. Fine manual control (fine motor precision and fine motor integration) and fine manual coordination (manual dexterity and upper limb coordination) were assessed pre and post treatment by Bruinisky Oseretsky test for motor proficiency (BOT-2). Results: There was a statistical significance improvement in fine manual control, manual coordination, and fine motor composite (fine manual control and fine manual coordination) post treatment compared with that pre-treatment in both groups (p>0.01). There was a statistical significance improvement in manual coordination and fine motor composite of study group compared with that of control group post treatment (p < 0.01), while there was no significant difference in fine manual control between groups post treatment (p > 0.05). Conclusion: Motor imagery may provide complementary training strategy that promotes movement planning, coordination, and execution precision among children with cerebral palsy. s
(3GdNdajI(B: (3jYJHQ VYa hXjaI GdjO hJfSjb GdWQa GdYdhj geG eTcdJGf QFjSjJGf JhGLgGf GdCWaGd GdeUGHjf HGdaGdL GdTbj GdZQV(B: (3jgOa GdYed GdMGdj Edi OQGSI JCKjQ GdJOQjH GdMQcj GdJNjdj Ydi hXjaI GdjO hJfSjb GdWQa GdYdhj dOi GdCWaGd GdeUGHjf HGdaGdL GdTbj(B. (3GdWQb(B: (3TGQcJ aj gPg GdOQGSg SJg h KdG KhJ WadG eUGkHG HGdaGdL GdTbj ef cdG GdLfSjf, JJQGhM CYeGQge ef SHY Edi GKfj YTQ YGkeG (B.(3Je GNJjGQge ef GdYjGOGJ GdNGQLjI Hcdjg GdYdGL GdWHjYj ,LGeYg GdbGgQg(B. (3dbO Je JhRjY GdGWaGd HTcd YThGFj Gdj eLehYJjf (B: (3GdeLehYI GdVGHWI heLehYI GdOQGSI(B. (3Jdbi GdCWaGd aj cdJG GdeLehYJjf HQfGeL YdGL WHjYj eUee HGdEVGaI Edi Pdc, Jdbi GdCWaGd aj GdeLehYI GdVGHWI HQfGeL YdGL hXjaj eUee NUjkUG dJMSjf hXjaI GdjO hJfSjb GdWQa GdYdhj, HjfeG Jdbi GdCWaGd aj eLehYI GdOQGSI JOQjkHG Ydi HQfGeL GdJOQjH GdMQcj GdJNjdj (B.(3Je ELQGA HQfGeL GdYdGL dcdG GdeLehYJjf deOI SGYI hGMOI, KdGK LdSGJ CSHhYkjG deOI GKfj YTQ CSHhkYG eJJGdkjG(B. (3Je Jbjje GdJMce GdjOhj GdObjb (B((3ObI GdMQcI GdObjbI hGdJcGed GdMQcj GdObjb(B) (3hGdJfSjb GdjOhj GdObjb (B((3GdHQGYI GdjOhjI hJfSjb GdWQa GdYdhj(B) (3bHd hHYO GdYdGL HGSJNOGe GNJHGQ (BBruinisky Oseretsky (3ddcaGAI GdMQcjI (B(BOT-2). (3GdfJGFL(B: (3cGf gfGc RjGOg PGJ OdGdg GMUGFjg aj GdJMce GdjOhj GdObjb h GdJJSjb GdjOhj h GdJQcjH GdMQcj GdObjb HYO GdYdGL ebGQfg HeG bHd GdYdGL (B(P>0.01 ) (3HGdEVGaI Edi Cfg gfGc RjGOg PGJ OdGdg GMUGFjg aj GdJfSjb GdjOhj h GdJQcjH GdMQcj GdObjb deLehYI GdOQGSg ebGQfg HeLehYg GdJMce HYO GdYdGL (B(P>0.01) (3aj Mjf de jcf gfGc aQb cHjQ aj GdJMce GdjOhj GdObjb Hjf GdeLehYGJ HYO GdYdGL (B(p>0.05). (3GdGSJfJGL(B: (3jYO GSJNOGe GdJOQjH GdMQcj GdJNjdj GSJQGJjLjI JOQjH Jcejdjg JYRR JNWjW GdMQcI hGdJfSjb hObI hXjag GdjO h GdWQa GdYdhj dOj GdGWaGd GdeUGHjf HGdaGdL GdTbj(B.s
Thesis (M.Sc)-Cairo University, 2025.
Bibliography: pages 81-95.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Physical Therapy; (3GdYdGL GdWHjYj s; Hand function -- Hemiplegic cerebral palsy -- Motor imagery -- Upper limb coordination